Características y distribución espacial de movimientos en masa rápidos en zonas de montaña (Alta Ribagorza, Pirineo Central) - Chueca Cia, Javier (Geographicalia, 2017)
The general features of the rapid mass movements identified in amountain area of the central Pyrenees (Aragonese Alta Ribagorza) are studied in this article, carrying out an inventory of its different tipologies and analysing its predominant spatial distribution patterns; in a complementary manner, a general risk cartography of the spaces of the area subjected to the action of these phenomena is made.